2021
DOI: 10.3389/fimmu.2020.583251
|View full text |Cite
|
Sign up to set email alerts
|

cGAMP/Saponin Adjuvant Combination Improves Protective Response to Influenza Vaccination by Microneedle Patch in an Aged Mouse Model

Abstract: Current strategies for improving protective response to influenza vaccines during immunosenescence do not adequately protect individuals over 65 years of age. Here, we used an aged mouse model to investigate the potential of co-delivery of influenza vaccine with the recently identified combination of a saponin adjuvant Quil-A and an activator of the STING pathway, 2’3 cyclic guanosine monophosphate–adenosine monophosphate (cGAMP) via dissolving microneedle patches (MNPs) applied to skin. We demonstrate that sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(74 reference statements)
0
12
2
Order By: Relevance
“…cGAMP has been applied alone or in combination with other molecular adjuvants in multiple vaccine studies in recent years. 18 , 50 , 51 Previous studies have detailed how cGAMP stimulates the STING-initiated downstream type I interferon signaling pathway and induces cytokine expression. The innate signaling features of cGAMP give it potential as a safe and promising adjuvant candidate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cGAMP has been applied alone or in combination with other molecular adjuvants in multiple vaccine studies in recent years. 18 , 50 , 51 Previous studies have detailed how cGAMP stimulates the STING-initiated downstream type I interferon signaling pathway and induces cytokine expression. The innate signaling features of cGAMP give it potential as a safe and promising adjuvant candidate.…”
Section: Discussionmentioning
confidence: 99%
“…cGAMP is a natural STING agonist with a negative charge and has been demonstrated as an effective adjuvant for influenza vaccines. 17 , 18 αGC is a potential mucosal adjuvant capable of inducing mucosal secretory IgA (sIgA) and systemic IgG responses against viral infections. 19 , 20 , 21 Nanoplatforms incorporating αGC activated iNKT cells and generated augmented antigen-specific CTL responses.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the combination of cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) and saponins, which improved protective response to influenza. Saponins can increase the permeability of cell membrane, allowing more cGAMP to enter the cells and increasing the utilization rate of saponins, leading to stronger immune effects ( 130 , 131 ). Furthermore, nasal delivery systems such as microspheres or nanospheres made of chitosan, PLGA (poly[D,L-lactic-co-glycolic acid]), alginate, or cross-linked dextran have been employed to encapsulate saponins for nasal administration ( 132 135 ).…”
Section: Future Perspective Of Saponin-based Adjuvantsmentioning
confidence: 99%
“…However, whether CDNs can effectively enhance specific immune responses in aged or newborns remains to be determined [ 131 , 136 ]. Borriello et al found that although cGAMP induced a comparable expression of surface maturation markers in newborn and adult BMDCs, cGAMP adjuvantation alone failed to increase HA-specific antibody responses in newborn mice [ 136 ].…”
Section: Cdns As Potent Vaccine Adjuvants For Systemic and Mucosal Immunizationmentioning
confidence: 99%